Food gardens and learning: Investigating food gardens as tools for academic instruction in Soweto, Johannesburg, South Africa - Moswane, Mafule (My University, 2018)
Community gardens offer one strategy for responding to food insecurity, poverty and community building, and can involve a wide range of groups. There has however been less research in South Africa to date on institutional food gardens in comparison with 'community' food gardens. Where there has, the focus has been on gardens' relations to feeding schemes and nutritional outcomes. There has been little investigation of the educational benefits offered by school gardens in South Africa. The purpose of this study was to investigate the relationship between food gardens and academic instruction, and how and why that varied across schools in Soweto, Johannesburg. Taking a qualitative and comparative approach, data was collected at two consenting schools using semi-structured interviews with teachers and participant observation. Using thematic analysis, my overall findings were that, while the gardens in both schools were used sometimes to supplement the food scheme or to punish students, the primary school showed some engagement with it for theoretical instruction as well as for recycling and creating compost while the secondary school did not use the garden for teaching and learning. Both schools faced a number of challenges in running their gardens as well as using them for teaching and learning. Despite these challenges, teachers, particularly newer ones, shared many possibilities of how the gardens could equip the learners with alternative skills that classroom education does not offer. With this clear interest in garden-based learning, it is worth investing in these sites through a multi-disciplinary approach and working together across garden coordinators, teachers and other involved stakeholders to realise their pedagogical potential.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, in fulfillment of the requirements for the degree of Master of Science in Geography and Environmental Studies
Keywords: Food gardens; Academic instruction,; Teaching and learning